Fiber reinforced scalelike MoSi2-borosilicate glass coating with improved contact damage resistance and thermal shock resistance. Issue 8 (15th April 2021) - Jiao, Mengyu; Wu, Jingyu; Guo, Linlin; Han, Pengda; Du, Haiyan; Hu, Xiaoxia
Abstract: On the surface of rigid mullite fiber ceramics, MoSi2 high emissivity coating with improved thermodynamic properties was prepared by the slurry method combined with the sol-gel method. The area and width of the cracks in the coatings crack network structure was reduced by adding fiber into the slurry. Besides, the discrete condition among scales in the scalelike crack network was improved. The morphology, contact damage resistance, thermal shock resistance, and infrared radiation characteristics of coatings were comprehensively researched. Results showed that fibers with an aspect ratio of 25–30 existed in cracks, connecting the adjacent scale areas, enhancing the bonding performance between scales, and avoiding the peeling of the coatings under an external force. As the area of the crack area reduced, the stiffness of the coatings increased. When a constant load was applied, the coatings remained intact and had a smaller residual displacement compared with coatings without fiber addition, which improved the reusability of the coatings. After 20 thermal cycles between 1300 °C and room temperature, the bonding strength of coatings was improved after adding fiber. Besides, the tensile fracture at the fiber tile indicated that the bonding strength of the coating and substrate was higher than the mechanical interlocking between the gradient layer and substrate. The total emissivity of all the coatings was higher than 0.92.